Corporate Board Diversity and Sustainability Reporting: Empirical Evidence from Indonesia Before and During COVID-19 - Nurma Juwita; Setianingtyas Honggowati (Journal of Accounting and Investment, 2022)
Research aims: This study aims to investigate how the influence of board diversity before and during the COVID-19 pandemic.Design/Methodology/Approach: The researchers used purposive sampling method. The research sample was 70 companies in the pre-pandemic period and 52 companies during the pandemic with the following criteria: all companies in Indonesia listed on the IDX that published complete sustainability reports and annual reports. In testing the hypotheses, multiple linear regression analysis was employed.Research findings: The presence of board diversity affected sustainability reporting in the pre-pandemic period, but during the pandemic, it did not affect the sustainability report disclosure.Theoretical contribution/Originality: This study is empirical evidence regarding the comparison of the effect of the presence of board diversity before the pandemic and during the pandemic.Research limitation/Implication: The sample period during the pandemic was still too short. As known that the initial COVID-19 pandemic entered Indonesia was in 2020, so the researchers experienced limited data regarding sustainability reports during the pandemic.